“Santa Teresa – this is my history”: the meaning of the process of assistance transformation for a patient living at a community house - Menezes, Adriana da Cunha; Pereira, Maria Alice Ornellas (Rev Rene, 2001)
The purpose of this study is to reach the semantic understanding of the process of assistance transformation for the patients of the Psychiatric Hospital Nursing Home in Ribeirão Preto. The history of life was used as instrument for a qualitative approach of research. The methodological-theoretical procedure of this study was based on observation, open interview and consultation of respective record. Analysing data, the following categories were involved: guilt, abandonment/alcoholism and the context of the psychiatric hospitalizations. Through the analysis, it was noticed that the first step towards the real changes was taken, however this also evinces the necessity of the continuing rehabilitation process.